ENHANCING DIGITAL LITERACY AMONG STUDENTS - Dian Widiarti; Nine Febrie Novitasari; Ahmad Yusuf Firdaus (Faculty of Letters Universitas Abdurachman Saleh Situbondo, 2025)
The rapid growth of digital technology requires students to develop strong digital literacy skills to navigate the internet responsibly, securely, and efficiently. However, many students still struggle with distinguishing credible information, safeguarding their personal data, and practicing proper online etiquette. This program was designed to improve the digital literacy of students at SMPN Satap 4 Panarukan through an interactive, hands-on awareness program. The approach involved a pre-test, instructional presentations, discussions, simulations, and a post-test to assess learning outcomes. The pre-test findings revealed that only 31% of the 32 students demonstrated a solid understanding of digital literacy. However, after the program, post-test results indicated a notable improvement, with 81% of students correctly answering questions and exhibiting a deeper comprehension. Moreover, student participation in discussions and simulations increased, reflecting the effectiveness of the chosen methods. Despite these positive outcomes, sustaining digital literacy remains a challenge due to limited technological access and the absence of consistent educator support. To address this, integrating digital literacy into the school curriculum and securing support from various stakeholders is crucial to ensuring students can continuously refine their digital skills.